Risk factors for requiring cholecystectomy for gallstone disease in a prospective population‐based cohort study. Issue 10 (25th May 2016) - Talseth, A.; Ness‐Jensen, E.; Edna, T.‐H.; Hveem, K.
Abstract : Background: The relationship between different lifestyle factors and the risk of needing cholecystectomy for gallstone disease is not clear. This study aimed to assess the association between anthropometric, lifestyle and sociodemographic risk factors and the subsequent risk of requiring cholecystectomy for gallstone disease during long‐term follow‐up in a defined population cohort. Methods: Data from a large population‐based cohort study performed from 1995 to 1997 were used (the second Norwegian Nord‐Trøndelag health study, HUNT2). Following HUNT2, from 1998 to 2011, all patients operated on for gallstone disease with cholecystectomy at the two hospitals in the county, Levanger Hospital and Namsos Hospital, were identified. A Cox proportional hazards model was used for multivariable risk analysis. Results: The HUNT2 cohort included 65 237 individuals (69·5 per cent response rate), aged 20–99 years. During a median follow‐up of 15·3 (range 0·6–16·4) years, 1162 cholecystectomies were performed. In multivariable analysis, overweight individuals (body mass index (BMI) 25·0–29·9 kg/m 2 ) had a 58 per cent increased risk of cholecystectomy compared with individuals with normal weight (BMI less than 25·0 kg/m 2 ). Obese individuals (BMI 30 kg/m 2 or above) had a twofold increased risk. Increasing waist circumference independently increased the risk of cholecystectomy. In women, current hormone replacement therapy (HRT) increased the risk, whereas hard physical activity and higher educational level were associated with reduced risk of cholecystectomy. Conclusion: High BMI and waist circumference increased the risk of having cholecystectomy for both sexes. In women, the risk was increased by HRT, and decreased by hard physical activity and higher educational level. Abstract : Associated with obesity and sedentary lifestyle